2010
DOI: 10.1038/ismej.2009.147
|View full text |Cite
|
Sign up to set email alerts
|

Developmental microbial ecology of the crop of the folivorous hoatzin

Abstract: The hoatzin (Opisthocomus hoazin) is a South American strict folivorous bird, with a crop microbial ecosystem that ferments dietary plants. Chicks progressively become independent from the adultfed regurgitated crop liquids, and we hypothesized that the crop bacterial ecosystem develops through ecological succession mechanisms, as they grow into adults. The aim of this work was to compare the crop bacterial community in hoatzins from three age groups: newly hatched chicks, juveniles and adults by sequencing 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 55 publications
0
55
0
Order By: Relevance
“…We found that in the first section there was a greater proportion of Proteobacteria, with this group decreasing its relative abundance toward the final region of the intestine, where Firmicutes represented a higher percentage of the sequences. While other studies indicate that the bacterial intestinal communities were dominated by Firmicutes (in the range of 22.6-100%) [3,20] and Bacteroidetes (in the range of 1.1-56%) [19,65], our results show that Firmicutes is the dominant bacterial phylum in the second and third sections of the gut of House Sparrows (Figure 2).…”
Section: Bacterial Composition Along the House Sparrow's Gutmentioning
confidence: 44%
See 1 more Smart Citation
“…We found that in the first section there was a greater proportion of Proteobacteria, with this group decreasing its relative abundance toward the final region of the intestine, where Firmicutes represented a higher percentage of the sequences. While other studies indicate that the bacterial intestinal communities were dominated by Firmicutes (in the range of 22.6-100%) [3,20] and Bacteroidetes (in the range of 1.1-56%) [19,65], our results show that Firmicutes is the dominant bacterial phylum in the second and third sections of the gut of House Sparrows (Figure 2).…”
Section: Bacterial Composition Along the House Sparrow's Gutmentioning
confidence: 44%
“…In the few wild birds that have been studied, bacterial communities were dominated by Firmicutes; however the second dominant phylum varied: Actinobacteria in Adelaide Penguins and Proteobacteria in Zebra-Finches [6,8]. In the Hoatzin (Ophistocomus hoatzin) a folivorous bird with crop microbial fermentation [20], the microbial community of the crop was dominated by Firmicutes and Bacteroidetes [20,21,22] while the bacterial communities of the foregut were dominated by Bacteroidetes and Actinobacteria, and contained a lower proportion of Firmicutes and Proteobacteria [21].…”
Section: Bacterial Composition Along the House Sparrow's Gutmentioning
confidence: 99%
“…However, the fact that bacterial communities in all gerbil groups have passed through similar seasonal changes suggest that these changes may not be linked to changes in the internal environment of the host. Other studies reported that microbial communities show high variability between host individuals, age groups and sexes and/or a relatively high temporal stability (Moran et al, 2005;Costello et al, 2009;Godoy-Vitorino et al, 2010;Oh et al, 2012;Yatsunenko et al, 2012;Faith et al, 2013;van Dongen et al, 2013;Kueneman et al, 2014;Leclaire et al, 2014). The lack of interindividual variations in the composition of bacterial communities in our study may result from the transmission of fleas between hosts via direct interactions, replacement of burrows or free dispersal (Krasnov, 2008).…”
Section: Mcfallmentioning
confidence: 47%
“…However, a recent study on the hoatzin crop, using DNA microarray techniques, documented for the first time the presence of phyla such as Aquificae, Coprothermobacteria, Thermodesulfobacteria and Caldithrix in a vertebrate gut system (Godoy-Vitorino et al 2010). These techniques will need to be replicated on mammalian gut contents to determine if these phyla are unique to the hoatzin crop.…”
Section: Diversity Of Avian Intestinal Microbesmentioning
confidence: 97%